Biodegradable microparticles and nanoparticles by electrospraying techniques - Guarino, Vincenzo; Wan Abdul Khodir, Wan Khartini; Ambrosio, Luigi (SAGE Publishing, 2012)
Purpose: Biodegradable microparticles and nanoparticles are receiving increased attention for their ability to serve as a vi- able carrier for site-specific delivery of genes, drugs and other biomolecules. Electrospraying represents a challenging tech- nology which allows for the preparation of biodegradable particles with high bioavailability, good encapsulation, controlled release and fewer toxic properties. Methods: chitosan and polycaprolactone (PcL) particles were processed via electrospraying with control of basic process parameters: voltage and flow rate. Results: PcL microparticles with spherical shape or flattened particles were obtained as a function of the concentration of the processed solutions, which affects evaporation and chain entanglement formation. chitosan nanoparticles with submi- crometric sizes were obtained by carefully adjusting voltage and flow rate, which enables the control of particle size and distribution. Conclusion: We evaluated the benefits of the electrospraying technique to control the morphology of biodegradable mic- roparticles and nanoparticles for drug-delivery applications. the implementation of simple technological solutions which combine the use of standard electrospraying and electrospinning by simultaneous or sequential steps, opens the way toward the development of new, interesting devices for drug-delivery applications such as tumor targeting and oral delivery.